Evaluating The Effectiveness Of Vaccination Programs In Reducing Pediatric Infectious Disease Burden Globally - S S, Dr. Kumaran; K, Dr. Akila; Dhanraj, Fabiola M; Kasi, Ms. Soundarya (Adolescência e Saúde, 2026)
Background: Fewer interventions in the field of public health can achieve this as well as vaccination programs in their role in preventing infectious disease in pediatrics and decreasing child morbidity and mortality globally. Regardless of the global efforts, regions with disparity in vaccine coverage are still facing a difference in disease burden. Objective: The objective of this study is to assess how effective vaccination programs are in mitigating the burden of infectious diseases among the pediatric population all over the world. Methodology: The study design was cross-sectional and analytical based on data collected through global health databases, immunizations history, and during survey of caregivers. To evaluate the relationship between vaccination coverage and the occurrence of the disease, statistical analyses were performed, such as correlation and regression. Findings: The findings suggest that doubling the vaccination rates correlates with a 40-percent decrease in the cases of the infectious diseases among children, and a 35-percent decrease in hospitalization rates. Areas that had immunizations over approximately the same territory had much better mortality rates and child health results in general. Conclusion: Immunization is important in the low-burden of pediatric infectious diseases across the world. To enhance child health outcomes, it is critical to strengthen immunization coverage and deal with disparities.